EFEKTIVITAS PEMBELAJARAN SAINS BERBASIS STEAM MELALUI LAMPION BALING-BALING UNTUK MENINGKATKAN KETERAMPILAN KERJA SAMA PADA PEMBELAJARAN IPA KELAS V SD - Syaharani, Fitri; Tasikin, Syariah; Puspita Sari, Dian; Hermita, Neni; Gusmida Syahrun Barokah, Rifqa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by the importance of developing students collaboration skills in science learning at the elementary school level. STEAM-based science learning through pinwheel lantern media was selected as an alternative learning approach that can provide active, concrete, creative, and collaborative learning experiences. This study aimed to analyze the effectiveness of STEAM-based science learning through pinwheel lantern media in improving the collaboration skills of fifth-grade students at SD Negeri 112 Pekanbaru. This study used a quantitative approach with a one-group pretest-posttest design. The research subjects consisted of 29 fifth-grade students. Data were collected through pretests, posttests, and observation sheets on collaboration skills. The data were analyzed using mean scores and N-Gain. The results showed that STEAM-based science learning through pinwheel lantern media was able to improve students collaboration skills in the moderate category. Students showed improvement in group participation, task distribution, discussion, mutual assistance, and responsible task completion. Therefore, STEAM-based science learning through pinwheel lantern media can be used as an alternative science learning approach to develop elementary school students collaboration skills.